Functional diversity of photobiological traits within the genus Symbiodinium appears to be governed by the interaction of cell size with cladal designation. Issue 2 (28th May 2015) - Suggett, David J.; Goyen, Samantha; Evenhuis, Chris; Szabó, Milán; Pettay, D. Tye; Warner, Mark E.; Ralph, Peter J.
Summary: Dinoflagellates of the genus Symbiodinium express broad diversity in both genetic identity (phylogeny) and photosynthetic function to presumably optimize ecological success across extreme light environments; however, whether differences in the primary photobiological characteristics that govern photosynthetic optimization are ultimately a function of phylogeny is entirely unresolved. We applied a novel fast repetition rate fluorometry approach to screen genetically distinct Symbiodinium types ( n  =   18) spanning five clades (A–D, F) for potential phylogenetic trends in factors modulating light absorption (effective cross‐section, reaction center content) and utilization (photochemical vs dynamic nonphotochemical quenching; [1 – C ] vs [1 – Q ]) by photosystem II (PSII). The variability of PSII light absorption was independent of phylogenetic designation, but closely correlated with cell size across types, whereas PSII light utilization intriguingly followed one of three characteristic patterns: (1) similar reliance on [1 – C ] and [1 – Q ] or (2) preferential reliance on [1 – C ] (mostly A, B types) vs (3) preferential reliance on [1 – Q ] (mostly C, D, F types), and thus generally consistent with cladal designation. Our functional trait‐based approach shows, for the first time, how Symbiodinium photosynthetic function is governed by the interplay between phylogenetically dependent and independent traits, and is potentially a means to reconcile complex biogeographic patterns of Symbiodinium phylogenetic diversity in nature.